1996
DOI: 10.1007/s002130050133
|View full text |Cite
|
Sign up to set email alerts
|

Activational effects of social stress on IV cocaine self-administration in rats

Abstract: The objective of the current studies was to investigate how social stress modulates IV cocaine self-administration. Specifically, an experimental protocol was developed in rats that assessed the impact of recurrent non-injurious social confrontations with an aggressive opponent on subsequent rate of cocaine self-administration behavior, maintained across a range of doses. Initially, the cocaine dose-effect function for intravenous self-administration was determined, reinforcing every fifth lever press (fixed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
3
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(137 citation statements)
references
References 35 publications
8
125
3
1
Order By: Relevance
“…Motor activation in response to novel stressors and experimentally elevated levels of transcription factors in the striatum correlate well with rapid acquisition of 'low dose' cocaine self-administration behavior (Piazza et al, 2000;Mantsch et al, 2001;Colby et al, 2003). Perhaps more pertinent to the acceleration of initial drug taking, even at higher doses, is the immediate activational effect of social stress (Tidey and Miczek 1997;Miczek and Mutschler, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motor activation in response to novel stressors and experimentally elevated levels of transcription factors in the striatum correlate well with rapid acquisition of 'low dose' cocaine self-administration behavior (Piazza et al, 2000;Mantsch et al, 2001;Colby et al, 2003). Perhaps more pertinent to the acceleration of initial drug taking, even at higher doses, is the immediate activational effect of social stress (Tidey and Miczek 1997;Miczek and Mutschler, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The tethered catheter supplied i.v. solutions from a counterbalanced swivel (Instech Laboratories) connected to an infusion pump (Med Associates Inc., St. Albans, VT) (for details, see Miczek and Mutschler, 1996). Catheters were flushed daily with heparinized saline (20 IU/ml), and during the light phase 0.17 ml pulses of saline were delivered every 30 min.…”
Section: Experiments 1: Cocaine Self-administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of investigators have demonstrated that stressors facilitate the acquisition of cocaine SA (see eg Goeders and Guerin, 1994;Haney et al, 1995;Miczek and Mutschler, 1996;Ramsey and Van Ree, 1993;Campbell and Carroll, 2001;Kosten et al, 2000;Schenk et al, 1987) and reinstate extinguished cocaine-seeking behavior (Erb et al, 1996;Ahmed and Koob, 1997;Mantsch and Goeders, 1999a;Shalev et al, 2003). By contrast, the ability of stress to produce escalating patterns of cocaine SA has not been extensively examined.…”
Section: Introductionmentioning
confidence: 99%
“…Similar enhancement of drug responses occurs when rats are exposed to stressors other than a novel environment (e.g., Refs. [1,24,30]). Much of the individual-differences research in rats has used amphetamine as the prototypical psychomotor stimulant.…”
mentioning
confidence: 99%